The urgency of green laboratory for sustainability: Review from Scopus AI data - H. Husamah; Abdulkadir Rahardjanto; Tutut Indria Permana; Ahmad Adnan Mohd Shukri; Burak Olur; Roimil Latifa (Universitas Muhammadiyah Malang, 2025)
Background: The increasing environmental burden of scientific laboratories has prompted a critical need to adopt sustainable practices. Laboratories consume substantial amounts of energy and water and generate hazardous and plastic waste, making them significant contributors to environmental degradation. Objectives: This study aims to explore the urgency, key themes, and strategic contributions of green laboratories to sustainability. Methods: Using a review approach supported by Scopus AI, the study collected and analyzed peer-reviewed data through natural language and keyword-based queries, combined with thematic mapping. Results: Key findings reveal four dominant themes: real-world labs, green chemistry, sustainability in higher education, and green technological innovation. These green lab practices offer benefits including reduced environmental footprint, cost savings, enhanced safety, and alignment with sustainability goals. However, challenges such as financial constraints and resistance to change must be addressed through stakeholder engagement and education. Conclusion: The study concludes that green laboratories play a vital role in sustainability transitions by bridging innovation, education, and environmental responsibility. This review offers a framework for future research and institutional efforts aimed at accelerating green lab adoption worldwide.